PENGGUNAAN MEDIA SOSIAL INSTAGRAM SEBAGAI GAYA HIDUP PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Winda Monica Silvia; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Social Media Instagram is a social media-based online that sole purpose to share a photo or video. With the use of Instagram certainly has fused and become part of everyday life. In life we can not be separated from his name lifestyle, lifestyle is a pattern of a person's life that can be seen from the activities, interests and opinion. This study aims to see the level of activity of the students of the Faculty of Social and Political Science University of Riau in using social media Instagram, as well as see the influence of the activity of the social media Instagram to the lifestyle of students of the Faculty of Social and Political Sciences, University of Riau. This research use method approach of quantitative inferential. The sampling method used is Proportional random cluster sampling. The theory used is the popular culture and lifestyle. The results obtained in the field of activity of the students in using social media Instagram, among others, post, follow, like, comment, mention and hastag overall including into the category of being. The activity of the social media Instagram to influence the life style of students of the Faculty of Social and Political Sciences, University of Riau this is evidenced by the value t count > t table ie 10,372 >1,969 so it can be concluded that H0 is rejected and Ha accepted. Furthermore, there is a positive influence between the variables of the activity of the social media Instagram to the lifestyle of students of the Faculty of Social and Political Sciences, University of Riau, it is based on the results of the value of the regression coefficient in this study is the value of Y = 10,535 + 0,396 X. The relationship between social media activity Instagram and lifestyle that are with the value of the Pearson Correlation 0,558. Based on the table “Model Summary” shows that the value of the coefficient of determination (r-square) is equal to 0,312 the figure shows the understanding that the donation of the influence of variable activity of the social media Instagram to the lifestyle of students of the Faculty of Social and Political Sciences, University of Riau is by jan 31.2% while the rest to 68.8% student lifestyle influenced by other variables not examined in this study e.g. media facebook, youtube, magazines and television. Keywords: Popular Culture, Social Media Instagram, Lifestyle